Plasmonic metal‐organic frameworks. (2nd July 2021) - Zheng, Guangchao; Pastoriza‐Santos, Isabel; Pérez‐Juste, Jorge; Liz‐Marzán, Luis M.
Abstract: Plasmonic metal‐organic frameworks are composite nanoparticles comprising plasmonic metal nanoparticles (NPs) embedded within a metal‐organic framework (MOF) matrix. As a result, not only the functionalities of the individual components are retained, but synergistic effects additionally provide improved chemical and physical properties. Recent progress in plasmonic MOFs has demonstrated the potential for nanofabrication and various nanotechnology applications. Synthetic challenges toward plasmonic MOFs have been recently addressed, resulting in new opportunities toward practical applications, such as surface‐enhanced Raman scattering, therapy, and catalysis. The impact of key parameters (thermodynamic vs. kinetic) on the synthetic pathways of plasmonic MOFs is reviewed, while providing insight into related progress toward structure‐derived applications. Abstract : Plasmonic metal‐organic frameworks hybrid nanocomposites feature improved chemical and physical properties, as compared with their individual components, due to synergistic performance. These materials show excellent opportunities toward practical applications, such as surface‐enhanced Raman scattering, therapy, and catalysis.